The demarcation between younger and older acute myeloid leukemia patients: A pooled analysis of 3 prospective studies. Issue 18 (24th June 2013) - Yanada, Masamitsu; Ohtake, Shigeki; Miyawaki, Shuichi; Sakamaki, Hisashi; Sakura, Toru; Maeda, Tomoya; Miyamura, Koichi; Asou, Norio; Oh, Iekuni; Miyatake, Junichi; Kanbayashi, Hiroyuki; Takeuchi, Jin; et al.
Abstract : BACKGROUND: Contemporary treatment protocols for adult acute myeloid leukemia (AML) are age‐specific, and older patients are generally treated less intensively than younger patients. However, it remains uncertain whether older but fit patients with AML really need to have their treatment attenuated. METHODS: To evaluate the contribution of age to outcome for patients with AML receiving intensive chemotherapy, data were analyzed for 2276 patients aged less than 65 years who were treated uniformly, regardless of age, in 3 consecutive prospective studies conducted by the Japan Adult Leukemia Study Group. RESULTS: A substantial drop in overall survival (OS) between patients aged 40 to 49 years and 50 to 64 years led to a focus on 2 comparisons: 1) age < 50 versus ≥ 50 years; and 2) age 50 to 54 versus 55 to 59 versus 60 to 64 years. OS was significantly better for patients aged < 50 years than that for those aged ≥ 50 years (49.6% and 37.0% at 5 years; P < .001); older patients were more susceptible to relapse, but not to early death or nonrelapse mortality. The significant differences in OS between these 2 age groups were equally seen for patients with favorable, intermediate, and adverse cytogenetics ( P < .001 each). Outcomes for those aged 50 to 54, 55 to 59, and 60 to 64 years were similar, with 5‐year OS rates of 38.2%, 35.1%, and 38.0%, respectively ( P = .934), and no differences in early death or nonrelapse mortality were observed among these age groups. CONCLUSIONS: These findings justify the use of intensive chemotherapy without dose attenuation toward older but fit patients with AML, at least up to the age of 64 years. Cancer 2013;119:3326–33 . © 2013 American Cancer Society . Abstract : Data were analyzed for 2276 patients who were treated uniformly regardless of age in 3 consecutive prospective acute myeloid leukemia studies. These findings justify the use of intensive chemotherapy without dose attenuation for older but fit patients with acute myeloid leukemia, at least up to the age of 64 years.